PELATIHAN Ms. OFFICE, ENGLISH FUN LEARNING ( EFL) DAN BELAJAR SAMBIL BERMAIN (BSB) DI TLANAKAN PAMEKASAN MADURA - Sandy Vikki Ariyanto; Fredy Yunanto; Idon Joni (COVIT (Community Service of Health), 2022)
Real Work Lecture (KKN) is an intra-curricular course organized by academics in all universities that must be followed by all students with the aim of increasing students' abilities and insights as a provision for life in society after graduating from study. Basically, Real Work Lecture (KKN) is a form of real dedication of a student to the real community. After getting lecture material that can always be useful in the community itself. English Fun Learning (EFL) and Learning While Playing (BSB) training services have been carried out. This service is carried out by the Service Team and KKN students. The place of this devotion is Tlanakan Pamekasan Madura. This service method uses 3 stages, namely Lecture, Discussion, Demonstration. The result of this service is an understanding of Ms. Office increased, increased learning outcomes using English Fun Learning (EFL), increased learning outcomes using Learning While Playing (BSB). Keywords: Training, EFL, BSB, Office, Tlanakan.